Assessing maximal oxygen uptake: creating personalized incremental exercise protocols simply and quickly - Ferri Marini, C.; Correale, L.; Carnevale Pellino, V.; Federici, A.; Vandoni, M.; Lucertini, F. (Strength and Conditioning Journal, 2021)
Measuring cardiorespiratory fitness (CF) is important for researchers, clinicians, and exercise practitioners to assess an individual's CF. One method of assessing CF is accomplished by measuring the maximal oxygen uptake during a personalized maximal graded exercise test (GXT). Tailoring a GXT protocol to a specific subject can be troublesome and time-consuming. In this article, simple and ready-to-use spreadsheets allowing the creation of individualized walking, running, and cycling GXT protocols are presented and explained. The procedures within the spreadsheets are based on the latest validated protocols, and the spreadsheets represent a time-saving, practical, and useful tool.